Domestic and International Models of Industry-Education Integration and Cooperative Education Model: A Comparative and Applied Study Based on Literature Review and Student Experience Survey - Zhabf, Mingyue; Fu, Ying (Journal of Educational Theory and Practice, 2026)
Against the backdrop of deepening industry–education integration and the transformation of applied talent cultivation, this study investigates collaborative education models in business administration programs. By comparing representative international models—including Germany’s dual system, the U.S. cooperative education model, and Singapore’s teaching factory—with domestic practices, and analyzing questionnaire data from 300 students involved in school–enterprise cooperation projects, the study develops a framework covering cooperative foundation, value co-creation behavior, learning outcomes, and continuous participation intention. Results show that resource complementarity and support, collaborative design and participation depth, and interactional fairness and trust significantly enhance learning outcomes, while value co-creation behavior partially mediates these relationships. Learning outcomes further strengthen students’ intention to continue participating. Although students generally hold positive perceptions of collaborative education, collaborative design and participation depth remain relatively weak. Comparative analysis indicates that international models demonstrate advantages in enterprise involvement, process-oriented evaluation, and institutionalized collaboration. Accordingly, this study suggests strengthening project-chain integration, process-oriented evaluation, and institutionalized collaboration mechanisms to improve the quality and effectiveness of industry–education integration in business administration education.